Plant Growth-Promoting Activity of Bacillus sp. PG-8 Isolated From Fermented Panchagavya and Its Effect on the Growth of Arachis hypogea - Gohil, Rinkal B.; Raval, Vikram H.; Panchal, Rakeshkumar R.; Rajput, Kiransinh N. (Frontiers in Agronomy, 2022)
A natural bacterial isolate that shows multiple plant growth-promoting activities was isolated from fermented panchagavya (a mixture of five indigenous cow products). It is a gram-positive, endospore-forming bacteria identified as Bacillus sp. PG-8 by 16S rRNA gene sequencing. The Bacillus sp. PG-8 have shown multiple plant growth-promoting activities as indole acetic acid (2.78 μg/ml), gibberellic acid (0.7 mg/ml), ammonia (6.51 μmol/ml), exopolysaccharide (2.6% w/v) production, and phosphate solubilization (198.27 μg/ml). The Bacillus sp. PG-8 has ability to survive under the abiotic stress conditions such as temperature (28–46°C), pH (5.0–12.0), salt (0.5–20.0% w/v NaCl), and osmotic resistance (1–10% w/v PEG-6000). Due to its diverse characteristics, the effect of Bacillus sp. PG-8 was tested on Arachis hypogea (groundnut). The seeds treated with Bacillus sp. PG-8 demonstrated a 70% germination rate with seedling vigor indexes of 154. In pot study, Arachis hypogea growth showed 1.38, 1.38, 1.32, 1.39, and 1.52 times increase in root hair number, leaf numbers, leaf width, leaf length, and leaf area, respectively. The addition of Bacillus sp. PG-8 culture to the Arachis hypogea plant resulted in a significant improvement in plant growth. Bacillus sp. PG-8 is a spore producer with stress tolerance and multiple plant growth-promoting properties, which makes it a potential liquid biofertilizer candidate.